Gene duplications, divergence and recombination shape adaptive evolution of the fish ectoparasite Gyrodactylus bullatarudis. Issue 8 (16th April 2020) - Konczal, Mateusz; Przesmycka, Karolina J.; Mohammed, Ryan S.; Phillips, Karl P.; Camara, Francisco; Chmielewski, Sebastian; Hahn, Christoph; Guigo, Roderic; Cable, Jo; Radwan, Jacek
Abstract: Determining the molecular basis of parasite adaptation to its host is an important component in understanding host–parasite coevolution and the epidemiology of parasitic infections. Here, we investigate short‐ and long‐term adaptive evolution in the eukaryotic parasite Gyrodactylus bullatarudis infecting Caribbean guppies ( Poecilia reticulata ), by comparing the reference genome of Tobagonian G. bullatarudis with other Platyhelminthes, and by analysing resequenced samples from local Trinidadian populations. At the macroevolutionary timescale, we observed duplication of G‐protein and serine proteases genes, which are probably important in host–parasite arms races. Serine protease also showed strong evidence of ongoing, diversifying selection at the microevolutionary timescale. Furthermore, our analyses revealed that a hybridization event, involving two divergent genomes, followed by recombination has dramatically affected the genetic composition of Trinidadian populations. The recombinant genotypes invaded Trinidad and replaced local parasites in all populations. We localized more than 300 genes in regions fixed in local populations for variants of different origin, possibly due to diversifying selection pressure from local host populations. In addition, around 70 genes were localized in regions identified as heterozygous in some, but not all, individuals. This pattern is consistent with a very recent spread of recombinant parasites. Overall, our results are consistent with the idea that recombination between divergent genomes can result in particularly successful parasites.